Prevention of Allergy to a Major Cow's Milk Allergen by Breastfeeding in Mice Depends on Maternal Immune Status and Oral Exposure During Lactation - Adel-Patient, Karine; Bernard, Hervé; Fenaille, François; Hazebrouck, Stéphane; Junot, Christophe; Verhasselt, Valérie (Frontiers in Immunology, 2020)
Background: The high incidence of food allergy in childhood points to the need of elucidating early life factors dictating allergy susceptibility. Here, we aim to address in a mouse model how the exposure to a major cow's milk allergen through breastmilk of mothers with different immune status influences food allergy outcome in offspring. Methods: BALB/cJ future dams were either kept naïve, or sensitized through the oral route using cholera toxin (“orally sensitized”) or through the i.p. route using alum (“i.p. sensitized”), or rendered fully tolerant (oral gavage without any adjuvant) to bovine β-lactoglobulin (BLG). After mating with naïve males and delivery, mothers were orally exposed or not to BLG during the whole lactation. Then, eight groups of lactating mothers were considered: naïve, i.p. sensitized, orally sensitized, or tolerant, each exposed or not during lactation. In order to specifically address breastmilk effects on their allergy susceptibility, pups from naïve-synchronized mothers were cross-fostered by the different groups of treated dams and lactating mothers at delivery. In some experiments, mothers kept their own pups to address a possible in utero effect. BLG antigen, BLG-specific antibodies, and BLG-immune complexes were measured in breastmilk from the different lactating mother groups. Allergic sensitization was monitored in 5-weeks old female offspring (n = 7–8/group of lactating mothers) by determining BLG-specific antibodies in plasma and splenocytes cytokine secretion after i.p. injections of BLG/alum. Allergic reaction to oral BLG challenge was evaluated by measuring mMCP1 in plasma. Results: Offspring was protected from one allergic i.p. sensitization when nursed by i.p. sensitized mothers, independently of BLG exposure during lactation. Orally sensitized dams conferred protection in offspring solely when exposed to BLG during lactation, while naïve mothers did not provide any protection upon BLG exposure. The levels of protection correlated with the levels of BLG-specific antibodies and BLG-immune complex in breastmilk. There was a trend for decreased sensitization in offspring breastfed by tolerant and exposed mothers, which was not associated with transfer of specific antibodies through breastmilk. Protection provided by nursing by treated/exposed mothers was not persistent after a boost i.p. injection of the progeny and then did not protect them from an allergic reaction induced at this time point. No additional in utero effects were evidenced. Conclusion: Our study demonstrates the strong potential of breastmilk to modulate immune response to a major cow's milk allergen in the progeny. It highlights the importance of maternal immune status and of her consumption of the allergen during lactation in dictating the outcomes in offspring. This opens perspectives where modulating maternal immune status might increase the chance of cow's milk allergy prevention in breastfed children.